Comprehensive Analysis of Expression and Prognostic Value of MS4As in Glioma - Zeng, Yingying; Tan, Peixin; Ren, Chen; Gao, Lianxuan; Chen, Yulei; Hu, Shushu; Tang, Nan; Chen, Chen; Du, Shasha (Frontiers in Genetics, 2022)
Glioma is the most common malignancy of the nervous system with high mortality rates. The MS4A family members have been reported as potential prognostic biomarkers in several cancers, however, the relationship between MS4A family and glioma has not been clearly confirmed. In our study, we explored the prognostic value of MS4As, as well as their potential pro-cancer mechanisms of glioma. Using bioinformatics analysis methods based on the data from public databases, we found that the expression of MS4A4A, MS4A4E, MS4A6A, MS4A7, TMEM176A and TMEM176B was significantly overexpressed in glioma tissues compared with normal tissues. The Kaplan-Meier method and Cox proportional hazards models revealed that high levels of MS4As led to a poorer prognosis; TMEM176A, TMEM176B, age, WHO grade and IDH status were identified as independent prognostic factors. Enrichment analysis predicted MS4As were related to tumor-related pathways and immune response, which may be the mechanisms of MS4As promoting tumorigenesis. Additionally, we analyzed the correlations of MS4As expression with immune cells and immune inhibitory molecules. Finally, our cellular experiment data suggested that knockdown of TMEM176B gene contributes to the decreased proliferation and migration of glioma cells. In conclusion, MS4A4A, MS4A4E, MS4A6A, MS4A7, TMEM176A and TMEM176B might be potential diagnosis or prognosis biomarkers in glioma and related to immune infiltrates in glioma.